2010
DOI: 10.1053/j.ajkd.2010.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Potassium Intake and Mortality in Long-term Hemodialysis Patients

Abstract: Background Hyperkalemia has been associated with higher mortality in long-term hemodialysis (HD) patients. There are little data concerning the relationship between dietary potassium intake and outcome. Study design Mortality-predictability of dietary potassium intake from reported food items, estimated from the Block Food Frequency Questionnaire (FFQ) at the start of the cohort, were examined in a 5-year (2001–06) cohort of 224 HD patients in Southern California using Cox proportional hazards regression. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
163
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 174 publications
(169 citation statements)
references
References 43 publications
3
163
1
2
Order By: Relevance
“…Noori et al found that the more potassium intake was associated with higher serum potassium level. 39 Consequently, the ideal window for MRAs administration may be at the end of the dialysis and far away from meals to avoid hyperkalemic episodes. Conclusively, we may safely consider using MRAs on patients receiving hemodialysis at a low dose at the end of the dialysis and far away from meal, but serum potassium levels need to be monitored closely, and the patients should be cautiously observed for potential side effects, which can be easily accomplished due to the regular visits to the hospital or dialysis center.…”
Section: Discussionmentioning
confidence: 99%
“…Noori et al found that the more potassium intake was associated with higher serum potassium level. 39 Consequently, the ideal window for MRAs administration may be at the end of the dialysis and far away from meals to avoid hyperkalemic episodes. Conclusively, we may safely consider using MRAs on patients receiving hemodialysis at a low dose at the end of the dialysis and far away from meal, but serum potassium levels need to be monitored closely, and the patients should be cautiously observed for potential side effects, which can be easily accomplished due to the regular visits to the hospital or dialysis center.…”
Section: Discussionmentioning
confidence: 99%
“…Since these patients have quite a reduced capacity to regulate the potassium level they will also be particularly vulnerable to even modestly increased dietary intake of potassium. In a clinical study following 224 hemodialysis patients for 5 years, the dietary potassium intake was determined by a FFQ (Noori et al, 2010). Analysed by quartiles, the potassium intake was determined to be 879, 1,342, 1,852 and 3,440 mg/day.…”
Section: Vulnerable Groupsmentioning
confidence: 99%
“…The original patient cohort was derived from a pool of Ͼ3000 MHD outpatients over 5 years in eight DaVita chronic dialysis facilities in the South Bay area of Los Angeles (see the NIED Study website at www.NIEDStudy.org for more details and previous publications (31)(32)(33). Inclusion criteria were outpatients who had been undergoing MHD treatment for at least 8 weeks, were 18 years of age or older, and signed the Institutional Review Board-approved consent form.…”
Section: Patient Populationmentioning
confidence: 99%